2016
DOI: 10.1111/eip.12407
|View full text |Cite
|
Sign up to set email alerts
|

Early psychosis intervention outpatient service of the 1st Psychiatric University Clinic in Athens: 3 Years of experience

Abstract: To present the 3-year experience of the early intervention in psychosis (EIP) service implementation of the 1st Psychiatric University Clinic in Athens. An overview of: (1) the purpose of our service, (2) the referral network, (3) the selection criteria, (4) the diagnostic procedures, (5) the therapeutic interventions and (6) the research activities. The service was established in 2012 and developed gradually aiming to provide information, early detection, treatment and support to people aged 15 to 40 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…38,39 Similar efforts are systematically organized also in Greece. 40,41 The significance of early intervention and development of prevention strategies for vulnerable populations are increasingly gaining ground in the military environment. 42 A recent study in the Greek army revealed that the duration of untreated psychosis is minimal for soldiers experiencing a first episode psychosis compared to the average time in the community.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Similar efforts are systematically organized also in Greece. 40,41 The significance of early intervention and development of prevention strategies for vulnerable populations are increasingly gaining ground in the military environment. 42 A recent study in the Greek army revealed that the duration of untreated psychosis is minimal for soldiers experiencing a first episode psychosis compared to the average time in the community.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 17 studies described the clinical activity of public mental health services providing intervention and early detection for young UHR patients: UK (M. Broome et al, 2005;Fusar-Poli et al, 2013), Greece (Kollias et al, 2016), France (Oppetit et al, 2016), Poland (Kotlicka-Antczak, PaweƂczyk, Rabe-JabƂo nska, & PaweƂczyk, 2015) and…”
Section: Participating Departmentsmentioning
confidence: 99%
“…The rate of transition to psychosis and the rate of psychosis relapse after 3 years was estimated to be 19.2% and 11.7% respectively. 27 The field about patients who are at a high risk of developing psychosis in Greece remains neglected since nothing else has been found to be reported or published. This finding could be interpreted in several ways.…”
Section: Early Intervention For Psychosis In Greecementioning
confidence: 99%